EFFECT OF HEAT TREATMENT ON THE BONDING QUALITY OF WOOD VENEERS TO PLYWOOD PRODUCTION - Ferreira, Bruno Santos [UNESP]; Campos, Cristiane Inacio de [UNESP]; Rangel, Elidiane Cipriano [UNESP] (Centro Pesquisas Florestais, Ufsm, 2018)
Plywood is a wood panel that can be used both in the furniture industry and in construction due to its structural use. However, to be used in construction, it needs to be resistant against wood decay agents and water, without compromising its mechanical properties. The heat treatment is an alternative treatment which improves the wood resistance to fungi and improves its dimensional stability. Thus, the objective of this study is to evaluate the influence of the heat treatment with three different temperatures, 160, 180 and 200 degrees C in the wettability of wood veneers and the shear strength in the bond line of the plywood produced with them. To do so, it was carried out the wettability testing using digital goniometer in the treated veneers at three temperatures and for the control specimen. Besides, it was carried out the shear strength in the bond line test, for testing the quality of bonding according to ABNT NBR ISO 12466-1 (2006). Because of the results obtained, it could be seen that the surface of the treated wood became more hydrophobic with increasing temperature, and this also resulted in a decrease in shear strength in the bond line, once the adhesive used (phenol-formaldehyde) is water based, however, the regulatory requirements have been met.
Keywords: temperature; wettability; Pinus taeda; shear strenght in the bondline